2016
DOI: 10.1002/pon.4135
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability and preliminary psychological benefits of mindfulness meditation training in a sample of men diagnosed with prostate cancer on active surveillance: results from a randomized controlled pilot trial

Abstract: While mindfulness training was found to be generally feasible and acceptable among participants who enrolled in the 8-week intervention as determined by completion rates and open-ended survey responses, the response rate between initial enrollment and the total number of men approached was lower than desired (47%). While larger sample sizes are necessary to examine the efficacy of mindfulness training on important psychological outcomes, in this pilot study posttraumatic growth was shown to significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 37 publications
1
71
0
Order By: Relevance
“…The 23 CTs included a total of 2,965 patients with a mean sample size of 129. 42 - 60 , 62 - 64 Of these, 21 studies reported post-treatment data, with 16 of these reporting relevant follow-up data. Two additional studies reported long-term (follow-up) data only.…”
Section: Resultsmentioning
confidence: 99%
“…The 23 CTs included a total of 2,965 patients with a mean sample size of 129. 42 - 60 , 62 - 64 Of these, 21 studies reported post-treatment data, with 16 of these reporting relevant follow-up data. Two additional studies reported long-term (follow-up) data only.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with an active control condition ( k = 9) tended to use attention and/or time‐matched designs, such as scripted calls inviting participants to describe their experiences of cancer diagnosis, treatment, and survivorship . One study gave participants randomized to the control condition a book describing mindfulness skills . The remainder of studies ( k = 10) used inactive control groups, such as waitlist control designs or usual care.…”
Section: Resultsmentioning
confidence: 99%
“…61 One study gave participants randomized to the control condition a book describing mindfulness skills. 72 The remainder of studies ( k = 10) used inactive control groups, such as waitlist control designs or usual care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are tools or potential interventions providers can share with their patients to help them process psychosocial stressors associated with their cancer diagnosis and management, including instruction in mindfulness meditation, cognitive-behavioral stress management, and diet and exercise lifestyle interventions [2426]. A study of one such lifestyle intervention conducted in California, US, found that men felt the program supported feelings of optimism, hope and well-being [27].…”
Section: Discussionmentioning
confidence: 99%